Precision cosmological constraints on atomic dark matter - Saurabh Bansal; Jared Barron; David Curtin; Yuhsin Tsai (Journal of High Energy Physics, 2023)
Abstract Atomic dark matter is a simple but highly theoretically motivated possibility for an interacting dark sector that could constitute some or all of dark matter. We perform a comprehensive study of precision cosmological observables on minimal atomic dark matter, exploring for the first time the full parameter space of dark QED coupling and dark electron and proton masses (α D , m e D $$ {m}_{e_D} $$ , m p D $$ {m}_{p_D} $$ ) as well as the two cosmological parameters of aDM mass fraction f D and temperature ratio ξ at time of SM recombination. We also show how aDM can accommodate the (H 0 , S 8) tension from late-time measurements, leading to a better fit than ΛCDM or ΛCDM + dark radiation. Furthermore, including late-time measurements leads to closed contours of preferred ξ and dark hydrogen binding energy. The dark proton mass is seemingly unconstrained. Our results serve as an important new jumping-off point for future precision studies of atomic dark matter at non-linear and smaller scales.